Granulocyte to monocyte ratio: leucokinetics in hematic biometry for appendicitis screening - Castillo-Martinez, Daniel Benito; Palacios-Rivera, Doris Michelle; Clemente-Castillo, Juan Antonio; Altamirano-Moreno, Karla Itzell; de los Cobos-Duran, Luis Daniel; Aragón Montes, Alejandro (International Journal of Research in Medical Sciences, 2023)
Background: Acute appendicitis diagnosis is still challenging and is established with clinical history, physical exam, laboratory tests, and imaging studies. It´s crucial to analyze the blood biometry with physiopathological asses and not with a statistical approach for establishing diagnostic items. The interaction between neutrophils with monocytes is noticeable in the blood biometry, so its relationship could be explained as directly proportional to the neutrophils count because of cellular recruitment and inversely proportional to the monocyte count because of cellular migration. Methods: A retrospective, transversal and analytic study was conducted, admission blood biometry of all patients (n=160) that went through appendectomy in Pemex´s North Central Hospital between 2014 and 2019 were dissected. Statistical correlation between sensibility and likelihood ratio of granulocyte/monocyte ratio (GMR), leucocyte elevation, and left shift of neutrophil count were contrasted. IBM® SPSS© statistical software performed the statistical analysis. Results: GMR (1.00) sensitivity showed to be superior to leukocytosis (0.785) and percentage neutrophils (0.846). the same for the negative likelihood ratios (LR-) calculated for GMR (0.00), leukocytosis (0.59) and percentage of neutrophils (0.579). Conclusions: GMR showed higher sensibility for detecting immune response in a patient with suspected acute appendicitis compared to leucocyte elevation and left shift of neutrophil count or both.